2008
DOI: 10.1002/bit.22006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of culture temperature on erythropoietin production and glycosylation in a perfusion culture of recombinant CHO cells

Abstract: To investigate the effect of culture temperature on erythropoietin (EPO) production and glycosylation in recombinant Chinese hamster ovary (CHO) cells, we cultivated CHO cells using a perfusion bioreactor. Cells were cultivated at 37 degrees C until viable cell concentration reached 1 x 10(7) cells/mL, and then culture temperature was shifted to 25 degrees C, 28 degrees C, 30 degrees C, 32 degrees C, 37 degrees C (control), respectively. Lowering culture temperature suppressed cell growth but was beneficial to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 37 publications
6
77
0
Order By: Relevance
“…To combat these negative effects, various strategies have been employed to reduce the levels of by-products and reduce the effects that these compounds have on CHO cell metabolism. For example, process parameters such as pH, temperature, CO 2 and osmolarity have been optimized [12][13][14], and complex feeding strategies have been devised using limited glucose and glutamine feeding, or feeding of other nutrients [15][16][17]. In addition, metabolism of CHO cells has been genetically engineered to enhance anaplerosis by overexpression of pyruvate carboxylase genes [18] and antiapoptotic genes such as Bcl-2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…To combat these negative effects, various strategies have been employed to reduce the levels of by-products and reduce the effects that these compounds have on CHO cell metabolism. For example, process parameters such as pH, temperature, CO 2 and osmolarity have been optimized [12][13][14], and complex feeding strategies have been devised using limited glucose and glutamine feeding, or feeding of other nutrients [15][16][17]. In addition, metabolism of CHO cells has been genetically engineered to enhance anaplerosis by overexpression of pyruvate carboxylase genes [18] and antiapoptotic genes such as Bcl-2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous research that has shown that the genes involved in the synthesis of the precursor oligosaccharide on the membrane of the endoplasmic reticulum are upregulated during the transition between growth stage 0 (G 0 ) and growth stage 1 (G 1 ). 101 In addition, Ahn and collaborators 100 found that at temperatures below 32 C, branching and sialic acid content of EPO produced in CHO cells decreased when compared to the glycoforms produced at 37…”
Section: Ammonia and Phmentioning
confidence: 99%
“…[98][99][100] These research groups have proposed that decreased temperatures maintain cell viability over longer periods of time, and that protein glycosylation occurs more efficiently under these high-viability conditions. This is consistent with previous research that has shown that the genes involved in the synthesis of the precursor oligosaccharide on the membrane of the endoplasmic reticulum are upregulated during the transition between growth stage 0 (G 0 ) and growth stage 1 (G 1 ).…”
Section: Ammonia and Phmentioning
confidence: 99%
“…pH causes GnTI, ManII, GalT and SiaT to mislocalize in Golgi [156] Viability, growth phase and temperature EPO/CHO:  branching at 32°C<T<37°C  temperature decreases UDPGlcNAc and UDP-GalNAc concentration [157] Serum and lipid supplements IFN /CHO:  branching with lipid supplementation…”
Section: Processmentioning
confidence: 99%